1987
DOI: 10.1016/s0735-1097(87)80230-9
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of left ventricular contraction and relaxation synchronism after recanalization of chronic total coronary occlusion by angioplasty

Abstract: Twenty patients with a chronic total coronary artery occlusion were studied before and 1 to 48 months (mean 9) after successful recanalization by angioplasty and compared with a group of 20 normal subjects. Before angioplasty, 19 of these 20 patients had angina. Collateral vessels to the distal part of the occluded vessel were visible in all 20 patients. A previous myocardial infarction was documented in 14 patients (9 with a Q wave and 5 with a non-Q wave infarction). At the time of follow-up, three patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(51 citation statements)
references
References 16 publications
2
46
0
3
Order By: Relevance
“…[25][26][27] Successful revascularization of coronary CTO is associated with the improvement of left ventricular function in patients with angina pectoris or old myocardial infarction. [28][29][30] Recently, George and colleagues reported that successful CTO intervention was associated with a decrease in mortality as compared to unsuccessful CTO intervention using large registry data (n = 13,443). 31) Furthermore, Jang and colleagues reported the long-term survival benefit of CTO revascularization as compared to medical therapy using a propensity score-matched population.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] Successful revascularization of coronary CTO is associated with the improvement of left ventricular function in patients with angina pectoris or old myocardial infarction. [28][29][30] Recently, George and colleagues reported that successful CTO intervention was associated with a decrease in mortality as compared to unsuccessful CTO intervention using large registry data (n = 13,443). 31) Furthermore, Jang and colleagues reported the long-term survival benefit of CTO revascularization as compared to medical therapy using a propensity score-matched population.…”
Section: Discussionmentioning
confidence: 99%
“…1,2) Although the treatment of CTO remains a technical challenge and still 20-35% of CTOs are not recanalized by percutaneous coronary intervention (PCI) even when performed by experienced operators, 3,4) successful PCI for CTO has been shown to improve left ventricular (LV) systolic function, reduce angina, increase exercise capacity, and reduce the need for late bypass surgery. 3,5,6) On the other hand, CTO patients who were not revascularized had a significantly higher rate of cardiac mortality and sudden cardiac death compared with those who were revascularized. 7,8) Moreover, in acute myocardial infarction (AMI) patients, the presence of CTO in a non-infarct-related artery (IRA) is a strong and independent risk factor for short-and middle-term mortality.…”
Section: Oronary Chronic Total Occlusion (Cto) Is Commonlymentioning
confidence: 99%
“…The remaining 353 patients were divided into two groups; patients with CTO (n = 25) and those without CTO (n = 328), and clinical indices including patient demographics, clinical and angiographic characteristics, and in-hospital and 30-day outcomes were compared. Cardiogenic shock on admission was defined according to the following clinical criterion used in the SHOCK trial: 5) hypotension defined as systolic blood pressure < 90 mmHg for at least 30 minutes or the need for supportive measures to maintain systolic blood pressure ≥ 90 mmHg, and end-organ hypoperfusion defined as cold extremities or a urine output of < 30 mL/hour and a heart rate ≥ 60 beat/minute. In-hospital management: Coronary angiography and subsequent PCI were performed immediately after the diagnosis of AMI.…”
Section: Oronary Chronic Total Occlusion (Cto) Is Commonlymentioning
confidence: 99%
“…The myocardium in the perfusion territory of a CTO can be functional, dysfunctional but viable, or dysfunctional and nonviable [3,4]. Dysfunctional but viable myocardium in CTO may have restored function after percutaneous coronary intervention (PCI) [5][6][7][8][9].…”
Section: Evaluation Of Left Ventricular Function After Percutaneous Rmentioning
confidence: 99%
“…Echocardiography was performed using a Philips IE33 ultrasound machine (Koninklijke Philips N.V., The Netherlands) with an M4S transducer according to the recommendations of the American Society of Echocardiography [4,13]. The percentage of the left ventricular ejection fraction (LVEF) was calculated by Simpson's biplane method of discs.…”
Section: Basic Echocardiographic Measurement and 2d-stementioning
confidence: 99%